Climate Change and Intertidal Wetlands - Pauline M. Ross; Paul Adam (Biology, 2013)
Intertidal wetlands are recognised for the provision of a range of valued ecosystem services. The two major categories of intertidal wetlands discussed in this contribution are saltmarshes and mangrove forests. Intertidal wetlands are under threat from a range of anthropogenic causes, some site-specific, others acting globally. Globally acting factors include climate change and its driving cause—the increasing atmospheric concentrations of greenhouse gases. One direct consequence of climate change will be global sea level rise due to thermal expansion of the oceans, and, in the longer term, the melting of ice caps and glaciers. The relative sea level rise experienced at any one locality will be affected by a range of factors, as will the response of intertidal wetlands to the change in sea level. If relative sea level is rising and sedimentation within intertidal wetlands does not keep pace, then there will be loss of intertidal wetlands from the seaward edge, with survival of the ecosystems only possible if they can retreat inland. When retreat is not possible, the wetland area will decline in response to the “squeeze” experienced. Any changes to intertidal wetland vegetation, as a consequence of climate change, will have flow on effects to biota, while changes to biota will affect intertidal vegetation. Wetland biota may respond to climate change by shifting in distribution and abundance landward, evolving or becoming extinct. In addition, impacts from ocean acidification and warming are predicted to affect the fertilisation, larval development, growth and survival of intertidal wetland biota including macroinvertebrates, such as molluscs and crabs, and vertebrates such as fish and potentially birds. The capacity of organisms to move and adapt will depend on their life history characteristics, phenotypic plasticity, genetic variability, inheritability of adaptive characteristics, and the predicted rates of environmental change.